Dietary patterns in human populations from northwest Patagonia during Holocene: an approach using Binford’s frames of reference and Bayesian isotope mixing models - Gordón, Florencia (2018)
The goal of this paper is to assess the variation in the proportional contribution of diverse resources to the diet of human populations from northwest Patagonia (Argentina) throughout the Middle-Late Holocene. Particularly, we assessed the variation among three geographic areas and two periods. We first estimated the expected proportions of terrestrial animals and plants and aquatic resources for each area according to the Binford’s frames of references approach. A Bayesian mixing method was then applied to calculate the proportion of plants and animals in the diets from stable isotopes (δ13C and δ15N) of human bone collagen. The isotope values suggest that the composition of diets differed spatially and temporally. Diets of South Mendoza were mainly composed of terrestrial animals (Rhea-Lama and rodents) with a greater incorporation of C3 plants towards the later Late Holocene; in North Neuquén, Rhea and Lama represent a proportion of 0.84 of the diet consumed; and finally, the sample of Center Neuquén is the only one with high values of Araucaria in the diet. The isotopic values obtained for the three studied areas did not fit to the expectations of Binford’s model, North Neuquén being the area that departs most from the predicted proportions of terrestrial animals and plants and aquatic organisms in the diet. These findings open up new questions about the local conditions that influenced regional variation in the diet of prehistoric hunter-gatherers.